EVALUATION OF PORTION STANDARDIZATION AT A FOODSERVICE IN A CHILD EDUCATION CENTER - Marcela Barthichoto; Andrea Carvalheiro Guerra Matias; Mônica Glória Neumann Spinelli; Edeli Simioni de Abreu (Universidade do Estado do Rio de Janeiro, 2015)
At any stage of human life appropriate nutrition is important,but in childhood it plays a decisive role. At this stage, there is anaccelerated process of growth and development, both physicaland psychomotor, which depends on a nutritionally balanced dietto occur normally. This study aimed to evaluate the pattern ofportioning offered to children in an educational center cafeteria.To assess whether portioning follows a homogeneous weightpattern, the portions were weighed four times for four days. Itwas used a digital scale with capacity of 5kg and precision of2kg. There was inadequate standardization of the serving sizesamong different age groups. In the analysis of the menu, therewas an adequate offer of macronutrients and dietary fiber, butinadequate offer of micronutrients. It is concluded that there ispoor serving size standardization, which leads to food oversupplyand remains. DOI: 10.12957/demetra.2015.14412